Human and environmental risk factors of leptospirosis in Gunungkidul, Indonesia: a case-control study - Sulistyawati, Sulistyawati; Pradana, Righa; Sugathan, Sandheep (International Journal Of Community Medicine And Public Health, 2020)
Background: Leptospirosis is a bacterial, zoonotic disease associated with environmental factors and human behavior related to occupation. This research aimed to investigate the association between human behavior and leptospirosis. Case mapping and topographical mapping were done for a comprehensive visualization. Methods: A matched case-control study design was conducted in Gunungkidul, Indonesia, from December 2017 to January 2018. Cases were selected from those reported as suspicious of leptospirosis by the Gunungkidul District Health Office during 2017 and controls were matched according to sex and age. Chi-squared, Fisher exact test, and Odds ratios were employed to find out the association between exposure and outcome for a significance level of 0.05. Quantum GIS-Web Map-Stamen terrain was used to overlay case and landscape. Results: Bivariate analysis showed that four exposure variables that enhanced the risk for leptospirosis though not significantly associated were history of injuries, habit of taking a bath or wash the clothes in the river, not using personal protection during work and presence of an animal fence surrounding the house. Most of the leptospirosis cases (>70%) resided in a hilly area. This finding assists in developing prevention strategies concerning leptospirosis infection. Conclusions: Human behaviour is vital in leptospirosis prevention. Accordingly, this study can broaden the understanding horizon, particularly for a decision-maker where and how to implement the Leptospirosis prevention program. Prevention should address the current situation in the field and based on population and local wisdom to result in the successful implementation.